ScreenFect A: an efficient and low toxic liposome for gene delivery to mesenchymal stem cells - Li, Liming; Ruan, Gui-Xin; HuangFu, Ming-Yi; Chen, Zhi-Lan; Liu, Hui-Na; Li, Linxian; Hu, Yu-Lan; Han, Min; Davidson, Gary; Levkin, Pavel; Gao, Jian-Qing (International journal of pharmaceutics, 2015)
Mesenchymal stem cells (MSCs) hold great promise in variety of therapeutic applications including tissue engineering and cancer therapy. Genetic modification of MSCs can be used to enhance the therapeutic effect of MSCs by facilitating a specific function or by transforming MSCs into more effective gene therapy tools. However, the successful generation of genetically modified MSCs is often limited by the poor transfection efficiency or high toxicity of available transfection reagents. In our previous study, we used thiol-yne click chemistry to develop new liposomal vectors, including ScreenFect® A (SF) (Li et al., 2012). In this study, we investigated the transfection performance of SF on MSCs.
Gesehen am 18.06.2020